1997
DOI: 10.1088/0022-3727/30/18/016
|View full text |Cite
|
Sign up to set email alerts
|

The unified interaction model applied to the gamma ray induced supralinearity and sensitization of peak 5 in LiF:Mg,Ti (TLD-100)

Abstract: We describe the development of a comprehensive theory of thermoluminescence (TL) supralinearity and sensitization, the unified interaction model (UNIM), based on both radiation absorption stage and recombination stage mechanisms. The UNIM incorporates both the track interaction model (TIM) for heavy charged particles (HCPs) and the defect interaction model (DIM) for isotropically ionizing gamma rays and electrons, in a unified and self-consistent conceptual and mathematical formalism. The model is applied to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…12(b)) TL intensity shows sublinearity. Linearity/sublinearity and even the decrease in TL intensity of yttria at higher doses can be explained by defect interaction model (DIM) [25,46]. TL glow peak temperature values are steady in throughout the studied dose range.…”
Section: Annealing Effectmentioning
confidence: 95%
See 3 more Smart Citations
“…12(b)) TL intensity shows sublinearity. Linearity/sublinearity and even the decrease in TL intensity of yttria at higher doses can be explained by defect interaction model (DIM) [25,46]. TL glow peak temperature values are steady in throughout the studied dose range.…”
Section: Annealing Effectmentioning
confidence: 95%
“…The increase in TL intensity may be attributed to the creation of defect centers such as F and F + centers. Decrease in TL intensity with increase of γ-dose may be ascribed to the formation of complex defects [25,46]. Also, explained by the defect interaction model [46].…”
Section: Annealing Effectmentioning
confidence: 96%
See 2 more Smart Citations
“…It is observed that, the TL intensity increases with γ-ray dose up to 6 kGy and then it decreases with further increase in dose (8-10kGy) (Fig.10). This increase in intensity can be explained on the basis of track interaction model (TIM) [30,31]. This model suggests that the number of generated traps as a result of irradiation depends on both the cross section of the tracks and the length of the tracks in the matrix.…”
Section: Electron Paramagnetic Resonance (Epr) Studiesmentioning
confidence: 99%